2011
DOI: 10.1039/c0lc00089b
|View full text |Cite
|
Sign up to set email alerts
|

Microarrays for the scalable production of metabolically relevant tumour spheroids: a tool for modulating chemosensitivity traits

Abstract: We report the use of thin film poly(dimethylsiloxane) (PDMS) prints for the arrayed mass production of highly uniform 3-D human HT29 colon carcinoma spheroids. The spheroids have an organotypic density and, as determined by 3-axis imaging, were genuinely spherical. Critically, the array density impacts growth kinetics and can be tuned to produce spheroids ranging in diameter from 200 to 550 µm. The diffusive limit of competition for media occurred with a pitch of ≥1250 µm and was used for the optimal array-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 46 publications
1
63
0
4
Order By: Relevance
“…[20][21][22] A spatially resolved analysis of drug response in 3-D models is of pivotal interest for anticancer compound research as gradients of hypoxia and nutrient distribution, which are observed in tumors and reproduced in tumor cell spheroids, influence the sensitivity towards anticancer drugs. 23 Since phototoxicity can interfere with anticancer drug effects, minimization of the light dose by SPIM again proves to be essential.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] A spatially resolved analysis of drug response in 3-D models is of pivotal interest for anticancer compound research as gradients of hypoxia and nutrient distribution, which are observed in tumors and reproduced in tumor cell spheroids, influence the sensitivity towards anticancer drugs. 23 Since phototoxicity can interfere with anticancer drug effects, minimization of the light dose by SPIM again proves to be essential.…”
Section: Discussionmentioning
confidence: 99%
“…The use of micropatterns that provide a controllable microenvironment for spheroid growth has been investigated in the past, but in 55 mm Petri dish format only. 25 Preliminary experiments investigated the effects of micropattern geometry, diameter, pitch, and cell-seeding density on HT-29 spheroid growth dynamics and size. Based on these initial results, a specific micropatterned 96-well plate was designed in which the dimensions and arrangement of the micropatterns addressed issues of (1) spheroid size heterogeneity, (2) the undesired detachment of spheroids during wash procedures or long-term growth, (3) spheroids touching and growing into one another as they expand, and (4) overcrowding that prevents optimal growth conditions for the production of large spheroids.…”
Section: Miniaturization Of Micropatterned Spheroid Formation and Growthmentioning
confidence: 99%
“…24 Native PDMS surfaces provide biologically inert backgrounds which resist cell adhesion. [26][27][28] Hydrophilic patterns for cell adhesion were provided within the microfluidic system by plasma stencilling using a Tesla generator. 22 As with the aqueous flows, the plasma was routed along the linear path of least resistance, oxidizing the surface to produce a hydrophilic state which supported cell adhesion, while the neighbouring hydrophobic PDMS surfaces confined cell adhesion to the trap regions.…”
Section: Single Cell Pairingmentioning
confidence: 99%